Pengaruh Gaya Hidup dan Citra Merek terhadap Keputusan Penggunaan Aplikasi Spotify (Studi pada Mahasiswa Universitas Dr. Soetomo) - Augustinah, Fedianty; Listyawati, Liling; Herawati, Andry; Alikah, Nur (Jurnal Bisnis Indonesia, 2024)
Given how many students use music applications on a daily basis, it is important to examine howlifestyle factors and brand image affect their choice of music application. Specifically, we will look athow lifestyle and brand image affect university students' decision to use the Spotify app. At Dr.Soetomo University. A quantitative survey approach with a causal associative nature is the studymethodology employed. Non-probability sampling is used in this sample technique. All independentvariables, including lifestyle and brand image, have a considerable impact on the decision to use theSpotify application, as demonstrated by the calculated F value > F table, or 71.024 > 3.09simultaneously. The findings of a contemporaneous test (the F Test) led to this conclusion. Comparingthe computed t values for the lifestyle variable (4.072) and the brand image variable (4.955) in thepartial test to the t table (1.984), each indicates a higher calculated t value. The fact that Ho isrefused while Ha is approved indicates that the deciding criteria of brand image (X2) and lifestyle(X1) have an impact on the decision to use the Spotify application (Y). The partial determination testyielded a partial determination coefficient (r2) of 0.201, or 20.1%, for brand image (X2) and 0.145,or 14.5%, for the lifestyle variable (X1). r2. The fact that the brand image variable's coefficient valueis higher than the lifestyle variable indicates that it has a bigger impact on people's decisions to usethe Spotify app.Keywords: Lifestyle; Brand Image; Usage Decisions; Spotify Application